KONSTITUTSIYA-DEMOKRATIYALIQ RAWAJLANIWDIN TIYKARI - Seytnazarov, S.M. (SCIENCE and SOCIETY, 2025)
The article discusses human rights and freedoms enshrined in our constitution, democratic reforms, modernization of the economy, and social changes. In particular, the issues of strengthening interethnic peace and harmony, and further development of historical and cultural traditions are emphasized.